Proteomic analysis of Bothrops pirajai snake venom and characterization of BpirMP, a new P-I metalloproteinase - Bernardes, Carolina P. (2013)
Bothrops pirajai snake venom was analyzed by a proteomic strategy. Proteins were separated by RP-HPLC, followed by SDS-PAGE, in-gel tryptic digestion, identification by MALDI-TOF/TOF mass spectrometry, and assignment to known protein families by similarity. Proteins belonging to six families were found in B. pirajai venom, including abundant PLA2s and metalloproteinases, with the remaining proteins distributed among l-amino acid oxidase, serine proteinase, disintegrin and lectin-like families. A P-I class metalloproteinase, named BpirMP, was isolated from this venom by three chromatographic steps. The enzyme has a molecular mass of 23.1 kDa, as determined by mass spectrometry. Its proteolytic activity on azocasein was inhibited by chelating and reducing agents, with optimum activity at higher pH values and 37 °C. BpirMP presented weak hemorrhagic activity, with an MHD of 50 μg, and was able to hydrolyze basement membrane components in vivo and in vitro. The toxin cleaved both Aα and Bβ chains of fibrinogen and was also able to degrade fibrin and blood clots in vitro. The primary sequence analysis indicates that BpirMP contains a zinc ligand motif and a CVM motif that is associated with a Met-turn structure. These results demonstrate that BpirMP is a zinc-dependent hemorrhagic metalloproteinase with fibrin(ogen)olytic and thrombolytic activities.